Incidence of HIV infection in eastern Uttar Pradesh: HIV counseling and testing services record based retrospective study - Singh, Amresh Kumar; Gaur, Vivek; Kumar, Ankur; Pandey, Jayesh; Upadhyay, Vandana (International Journal of Research in Medical Sciences, 2019)
Background: India has approximately 2.4 million of people living with HIV and out of these two thirds live in rural areas. This study may yield significant data to understand epidemiology of HIV/AIDS in this region that would help in designing techniques for effective implementation to prevent this infection. Methods: The present study was a comprehensive retrospective hospital-based investigation of the HIV infection in eastern Uttar Pradesh, India based on a large number of clinical samples at HCTS centre, representing different geographic regions and has been functional since 2002, conducting HIV tests, counselling of patients as well as maintains proper records. Results: A total of 444 HIV positive clients were registered in this retrospective study. The male and female ratio among all positive clients was 1.67:1 and the most common age group for both the genders was 35-49 years. Among 444 HIV positive clients, HIV-TB co-infection found in 72 (16.21%) cases. Out of 444 clients, 177 (40%) and 167 (38%) found extremely immunocompromised with low CD4 cells count in range between of 0-100 cells/mm3 and >100-350 cells/mm3 respectively. Mortality was seen in 72 (16%) out of 444 HIV positive clients. Conclusions: There is an urgent need of information, education about this disease and by providing suitable occupation or to make them aware, which will markedly help in preventing the spread of HIV pandemic in this geographical region.